Tears and saliva as alternative matrices for minimally invasive assessment of acute stress and pain in sheep - Rachidi, Fanny; Wagner, Romy; Fieseler, Helena; Kaiser, Matthias; Müller, Hendrik; Bittner-Schwerda, Lilli; Podpečan, Ožbalt; Mielenz, Norbert; Gottschalk, Jutta; Einspanier, Almuth; Möbius, Gerd; Starke, Alexander (Frontiers in Veterinary Science, 2026)
This study evaluated tears and saliva as alternatives to blood for determining cortisol concentration in healthy and chronically lame Merino meat sheep with dermatitis interdigitalis contagiosa (DINCO). Twelve healthy (HEALTHY) and 36 sheep with DINCO were included. After enrollment and placement of a jugular vein catheter on day 0, sheep underwent daily clinical examination and tear, saliva, and blood sampling on days 1 to 6 to determine cortisol concentrations (tears: COT; saliva: COS; blood: COB). After a 4-day adaptation period, blood and tears were collected six times at defined intervals immediately after the application of standardized stressors during a 1-h treatment phase. Sheep with DINCO were randomly allocated to one of three treatment groups and underwent claw treatment with or without pain control: the XYLA-IVRA group received sedation and retrograde intravenous regional anesthesia (IVRA); the IVRA group underwent IVRA and received a placebo instead of sedation; the PLACEBO and HEALTHY groups received isotonic saline instead of sedation and IVRA. The HEALTHY group underwent sham claw treatment. Statistical analyses used linear mixed models (PROC MIXED, SAS 9.4). Saliva and tear collection was minimally invasive, repeatable, and consistently yielded sufficient material for analysis without adverse health effects. Cortisol was detected in saliva and tears at all time points, and concentrations did not differ between healthy and diseased sheep during the adaptation phase. Both matrices had lower concentrations than blood but correlated positively and significantly with each other (day 2, R = 0.86 ± 0.05) and with COB (RCOB−COS = 0.71 ± 0.1, RCOB−COT = 0.61 ± 0.1). During the treatment phase, the COT increased in response to stressors similar to COB, albeit with a median delay of 6 min. The COT tended to be higher in the PLACEBO than in the XYLA IVRA group. Considering the time delay, saliva and tears are reliable, minimally invasive collected alternatives to blood for determining cortisol concentrations and assessing an acute stress response in healthy and chronically lame sheep.